Stereotactic ablative radiotherapy (SABR) for treatment of central and ultra-central lung tumors. Issue 1 (July 2015) - Chaudhuri, Aadel A.; Tang, Chad; Binkley, Michael S.; Jin, Michelle; Wynne, Jacob F.; von Eyben, Rie; Hara, Wendy Y.; Trakul, Nicholas; Loo, Billy W.; Diehn, Maximilian
Highlights Study of central lung tumors treated with stereotactic ablative radiotherapy (SABR). We define "ultra-central" to refer to tumors directly abutting the central airway. Ultra-central tumor patients have good outcomes and low treatment-related toxicity. RTOG 0813 central airway constraints may be stricter than necessary.